Enhencing Students’ Speaking Skill Through Youtube Video Presentation - Syamsia (LINGUISTICA, 2025)
Speaking is a productive skill. As a second and foreign language, learning speaking is considered to be difficult among the four skills because there many things that we have to consider in speaking. the students of English Department have problems in speaking skill. So the researcher using youtube video presentation to enhance their speaking. The statement of the problem was how is the students’ speaking skill be enhance by using youtube video presentation. The researcher used pre experimental design with non-equivalent control group design. The population were all students’ of English Department. The sample were 20 students. The data collected by using pretest and post-test. The data collected will be analyze based on scoring the students’ performance in youtube video presentation, calculating the mean score,and the see the comparison score in pretes and posttest. The result of post-test shows significant improvements in speaking score compared to the result of pre-test. in pretest, most of the students were in the poor and fair classification, just two students got good classfication. while in post test, two students got excelent classification, eight students got very good, eight students got good , and just one students got fair classification. The researcher can concluded that YouTube video presentations could enhance students' speaking skills.. it supports the notion that video presentations can be a valuable tool for language learning . YouTube video presentations offer an opportunity for students to engage with authentic language use and real-world contexts.